Passive smoker exposure as a risk factor of otitis media with effusion in children - Rizaldi, Riza; Tamin, Susyana; Dwi Restuti, Ratna; Suwento, Ronny; Parmaditya Pamungkas, Indra; Mansyur, Muchtaruddin (International Journal of Public Health Science (IJPHS), 2024)
Otitis media with effusion (OME) is a middle ear disorder often found in children and can cause hearing loss, delayed language acquisition, and behavioral disorders. Cigarette smoke exposure is one of the environmental factors that may raise the incidence of OME. This study aimed to identify the prevalence of OME and the risk of cigarette smoke to OME using urinary cotinine level examination, along with the characteristics of smoking history in the family. This cross-sectional study included 398 children aged 0-14 who underwent history taking, questionnaire completion, ear/nose/throat (ENT) examination, and tympanometry. OME patients based on ENT and tympanometry examination underwent urinary cotinine examination using lateral flow chromatographic immunoassay technique. Of the 398 children, five children were diagnosed with OME. The prevalence rate of OME was 1.3%. No OME patients were exposed to cigarette smoke based on urine cotinine levels of >200 ng/mL. However, based on history taking, one of five patients with OME is a passive smoker, with characteristics of active smoking history in the family one person (the father). In conclusion, there was no proportion of positive urinary cotinine levels in children with OME.